Metal Deposition at the Liquid–Liquid Interface. Issue 6 (6th August 2014) - Dryfe, Robert A. W.; Uehara, Akihiro; Booth, Samuel G.
Abstract Metal nanoparticles are readily formed, with a reasonable degree of size and shape control, using solution‐based reduction methods under ambient conditions. Despite the large number of reports in this field, much of our knowledge of nanoparticle growth is largely empirical, with the relationship between particle form and growth conditions, for example, still not well understood. Many nanoparticle preparation routes actually depend on not one, but two, solution phases, i.e. the syntheses involve reaction or transfer at the liquid–liquid (organic–water) interface. This interface can be polarised electrochemically, an approach that offers promise as a route to better understanding, and ultimately control, of nanoparticle growth.